Profile of urinary tract infections in the Urology Polyclinic of Imelda Pekerja Indonesia General Hospital - Matondang, Lasma Ani Giot Marito; Ade Indra Mukti; Edlin, Edlin (Buletin Kedokteran & Kesehatan Prima, 2024)
Urinary tract infection (UTI) is one of the most common infectious diseases in the world, affecting 150 million people every year.The purpose of this study was to determine the profile of urinary tract infection patients in the urology polyclinic at Imelda Pekerja Indonesia General Hospital.The type of research used in this study was observational analytic with a cross sectional study design. In this study, the population and sample included patients who experienced UTI infection at Imelda Pekerja Indonesia General Hospital. Univariate and bivariate analyses were performed. The results showed that sex was a significant risk factor for UTI. High-risk female gender can increase risk of UTI 4.442 times. Age was not a significant risk factor for UTI. Occupation was not a significant risk factor for UTI. A history of DM was not a significant risk factor for UTI. High-risk patients with a history of DM can increase risk of UTI 1.462 times, this risk was not statistically significant. A history of BSK is a significant risk factor for UTI. High-risk patients with a history of UTI can increase risk of UTI 4.929 times, this risk is statistically significant. Sex and a history of BSK were significant risk factors for UTI. Age, occupation, and history of DM were not significant risk factors for UTI.